Loving Edie : how a dog afraid of everything taught me to be brave - May, Meredith (Park Row Books, 2022)
"Edie is an unusually anxious dog. She cowers around most people and the slightest noise sends her into a frenzy. Edie's fears become so intense that May can't leave the house. Is this normal puppy behavior or something more? May grows determined to fix Edie, but what will she do if Edie can't be fixed? In this poignant and heartfelt memoir, May shares her unforgettable journey with Edie, and the lessons about selflessness and unconditional love that she learns along the way. From treating Edie with CBD gummies to visiting a dog medium, May shows just how far she is willing to go to save her dog. But maybe Edie is secretly the one doing the saving, if May will only open her heart."--Jacket